The Pharmacology of TD-8954, a Potent and Selective 5-HT4 Receptor Agonist with Gastrointestinal Prokinetic Properties - Beattie, David T.; Armstrong, Scott R.; Vickery, Ross G.; Tsuruda, Pam; Campbell, Christina B.; Richardson, Carrie; McCullough, Julia; Daniels, Oranee; Kersey, Kathryn; Li, Yu-Ping; Kim, Karl H. (Frontiers in Pharmacology, 2011)
This study evaluated the in vitro and in vivo pharmacological properties of TD-8954, a potent and selective 5-HT4 receptor agonist. TD-8954 had high affinity (pKi = 9.4) for human recombinant 5-HT4(c) (h5-HT4(c)) receptors, and selectivity (> 2,000-fold) over all other 5-HT receptors and non-5-HT receptors, ion channels, enzymes and transporters tested (n = 78). TD-8954 produced an elevation of cAMP in HEK-293 cells expressing the h5-HT4(c) receptor (pEC50 = 9.3), and contracted the guinea pig colonic longitudinal muscle/myenteric plexus (LMMP) preparation (pEC50 = 8.6). TD-8954 had moderate intrinsic activity (IA) in the in vitro assays. In conscious guinea pigs, subcutaneous (s.c.) administration of TD 8954 (0.03 - 3 mg/kg) increased the colonic transit of carmine red dye, reducing the time taken for its excretion. Following intraduodenal (i.d.) dosing to anesthetized rats, TD 8954 (0.03 - 10 mg/kg) evoked a dose-dependent relaxation of the esophagus. Following oral administration to conscious dogs, TD 8954 (10 and 30 µg/kg) produced an increase in contractility of the antrum, duodenum and jejunum. In a single ascending oral dose study in healthy human subjects, TD-8954 (0.1 - 20 mg) increased bowel movement frequency and reduced the time to first stool. It is concluded that TD-8954 is a potent and selective 5-HT4 receptor agonist in vitro, with robust in vivo stimulatory activity in the gastrointestinal (GI) tract of guinea pigs, rats, dogs and humans. TD-8954 may have clinical utility in patients with disorders of reduced GI motility.